Analisis Determinan Kepuasan Bekerja Tenaga Kerja yang Bekerja pada Getting Income Globally Economy di Kecamatan Masaran Kabupaten Sragen - Tika Destik Tristiyanti; Sunarso (Teewan Journal Solutions, 2026)
The gig economy in Masaran District, Sragen Regency, is growing rapidly, driven by the rise of app-based jobs and freelance services, which offer flexibility to workers. However, these opportunities pose challenges related to job satisfaction, such as income uncertainty, work environment conditions, and the need for trust. This is crucial to research because job satisfaction influences motivation and job sustainability. Therefore, this study focuses on analyzing the determinants of job satisfaction among workers in the gig economy in the region. Data collection methods included questionnaires and documentation.. This study was conducted in Masaran Subdistrict, Sragen Regency. The population consisted of workers working in the gig economy sector. A purposive random sampling method was used, with 96 respondents participating. The study found a significant positive effect of flexibility, income, work environment, and trust on job satisfaction among gig economy workers in Masaran District, Sragen. 91.40% of job satisfaction among gig economy workers in Masaran Subdistrict can be explained by the variables flexibility, income, work environment, and trust. The remainder is explained by factors outside this research model.